2021
DOI: 10.3390/coatings11070810
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Properties of Strontium Functionalized Titanium Surfaces for Oral Applications, A Systematic Review

Abstract: The aim of this systematic review was to assess the current scientific evidence of the antimicrobial potential of strontium (Sr) when used to functionalize titanium (Ti) for oral applications. Out of an initial list of 1081 potentially relevant publications identified in three electronic databases (MEDLINE via PubMed, Scopus, and Cochrane) up to 1 February 2021, nine publications based on in vitro studies met the inclusion criteria. The antimicrobial potential of Sr was investigated on different types of funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Therefore, the newly developed Sr-TCP coatings seem to induce a delay in cell growth, but not a killing effect against planktonic cells. Similar with our results, previous studies investigating the antibacterial properties of strontium revealed a limited early inhibition of the bacterial growth ( Alshammari et al, 2021a ). The authors attributed this observation to a slow kinetic of release of Sr ions in the medium during bacterial growth.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the newly developed Sr-TCP coatings seem to induce a delay in cell growth, but not a killing effect against planktonic cells. Similar with our results, previous studies investigating the antibacterial properties of strontium revealed a limited early inhibition of the bacterial growth ( Alshammari et al, 2021a ). The authors attributed this observation to a slow kinetic of release of Sr ions in the medium during bacterial growth.…”
Section: Resultssupporting
confidence: 93%
“…Strontium is a chemical element that is widely used for various applications in different industries. Strontium has been used as co-metal in the functionalization of silver-modified titanium implant surfaces thanks to its ability to lower the cytotoxic effect of silver towards the host cells without altering the antimicrobial properties and to promote osseointegration and bone regeneration ( Zhao et al, 2020 ; Alshammari et al, 2021a ; Baheiraei et al, 2021 ). Recently, some indications on the antibacterial properties of this metal have been reported, indicating strontium as a promising alternative to traditional antibiotics ( Alshammari et al, 2021a ; 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, a great interest has risen in substances with dual functionality, biofilm control as well as cell compatibility. In a recent study, the antimicrobial potential of strontium hydroxide against pathogenic oral bacteria was demonstrated [ 23 ], and related reviews reported the antimicrobial effects of functionalized surfaces with silver, strontium, or combinations of both [ 13 , 33 ]. Therefore, the aim of the present study was to systematically describe a therapeutic window for the application of silver and strontium salts on tissue cells and pathogenic bacteria of the oral cavity for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…In the same mono-culture setups, the cytocompatibility and antibacterial potential of strontium acetate were also tested. Despite the beneficial osteogenic effects of strontium, which have been extensively investigated, only a few studies evaluated the bactericidal effect of strontium against pathogenic oral bacteria [ 23 , 33 ]. In the present study, a minimum inhibitory concentration of SrAc (5 mg/mL) against A. actinomycetemcomitans after 24 h of incubation was defined.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Sr-doped HAp exhibits antibacterial activity due to the release of strontium ions, which might inhibit bacterial activities, including growth and reproduction, cell metabolism, and cell wall synthesis. [18][19][20][21] Fluorine also possesses some antibacterial properties, while the exact mechanisms remain unclear. [18,22] Moreover, strontium has a synergistic antibacterial effect with fluorine.…”
Section: Introductionmentioning
confidence: 99%